2017
DOI: 10.17977/um005v1i12017p085
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of Special Education in Improving Self Help Of Children with Special Need

Abstract: Effective special educational delivery for children with special needs is very crucial and pertinent for the development of the children's growth, knowledge and living skills. Special Education is indeed a volatile and changeable field and very dynamic as it constantly needs to change and reorient to cater the needs of special children. In anticipation of the global changes in the 21 st century, educating children with special needs is no longer confined within the four walls but is an education that needs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Salah satu bagian penting yang mendukung pelaksanaan pendidikan bagi penyandang disabilitas adalah Bimbingan Konseling (BK). Penyandang disabilitas dengan karakteristik uniknya berpotensi mengalami banyak permasalahan dan tantangan selama melaksanakan kegiatan belajar, sehingga keberadaan BK sangat penting dalam membantu penyandang disabilitas mengatasi masalahmasalah tersebut (Hussain & Maarof, 2017).…”
Section: Pendahuluanunclassified
“…Salah satu bagian penting yang mendukung pelaksanaan pendidikan bagi penyandang disabilitas adalah Bimbingan Konseling (BK). Penyandang disabilitas dengan karakteristik uniknya berpotensi mengalami banyak permasalahan dan tantangan selama melaksanakan kegiatan belajar, sehingga keberadaan BK sangat penting dalam membantu penyandang disabilitas mengatasi masalahmasalah tersebut (Hussain & Maarof, 2017).…”
Section: Pendahuluanunclassified
“…Another study by Hussain and Maarof (2017) indicated that self-development, social interaction, and social comparison are the chief elements of building a child's positive self-concept. Mostly, children spend half of their time in schools and are exposed to numerous challenges; it is easy for institutors to emphasize on social comparisons of normal students vs. special students.…”
Section: Self-concept and Social Integration Of Students With Special Education Needsmentioning
confidence: 99%
“…Thus, goal of this research is to develop learning package from education to development continues to improve teacher knowledge about special education about education for development sustainable. Interventions and the quality of education services provided for students with special needs determine a good future for them (Hussain &;Maarof, 2017).…”
Section: Introductionmentioning
confidence: 99%